Лучшие помощники
- Megamozg 2205 б
- Matalya1 1800 б
- DevAdmin 1720 б
- arkasha_bortnikov 895 б
- Dwayne_Johnson 860 б
14 мая 2023 09:21
232
y(0) = 1/2 cos 0 - 3 =
y(π/6) = 1/2 cos π/6 - 3 =
y(π/3) = 1/2 cos π/3 - 3 =
y(π/2) = 1/2 cos π/2 - 3 =
y(2π/3) = 1/2 cos 2π/3 - 3 =
y(5π/6) = 1/2 cos 5π/6 - 3 =
y(π) = 1/2 cos π - 3 =
y(7π/6) = 1/2 cos 7π/6 - 3 =
y(4π/3) = 1/2 cos 4π/3 - 3 =
y(3π/2) = 1/2 cos 3π/2 - 3 =
y(5π/3) = 1/2 cos 5π/3 - 3 =
y(11π/6) = 1/2 cos 11π/6 - 3 =
y(2π) = 1/2 cos 2π - 3 =
1
ответ
It looks like you have provided a set of initial conditions for a function y(x). Each initial condition specifies the value of y at a particular value of x. To fully determine the function y(x), we would need more information, such as an equation or formula that relates y and x. Without this additional information, we cannot say much more about the function y(x).
0
·
Хороший ответ
14 мая 2023 09:27
Остались вопросы?
Еще вопросы по категории Математика
ЗАДАНИЕ 4 1. Выпишите, раскрывая скобки, ряд, во всех словах которого пишется НН. В выписанном ряду для каждого случая укажите условия выбо...
Сколько ньютонов в одном килоньютоне?...
Что определяет внутреннюю энергию тела?...
Что такое первая декада месяца?...
Решить уравнение х-9=7 и х+30=70...